An investigation of the Ugandan publication Red Pepper: a case study from 2001-2004 - Opolot, Benedict (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2008)
Red Pepper has been the subject of much discussion in Uganda, with some accounts describing it as a liberal mouthpiece, and others as pornography. This case study, therefore, sought to investigate Red Pepper as a media phenomenon in Uganda in the 21st century, specifically between 2001 and 2004. Employing quantitative and qualitative methodologies, it focused on the production process and the text. Although sexualised content dominate its pages, and news about issues such as the environment and education are near-absent, its managers describe the publication as legitimate, normative and consistent with liberal media standards. Accordingly, to interrogate Red Pepper in terms of its journalistic functions, selected debates associated with liberal approaches to news media, media political economy, tabloidisation, pornography and gendered relations were reviewed. The analysis entailed five phases. The first was a denotative or descriptive analysis, which focused on the publication's structure and content focus. This was followed by an interview with management, a broad content analysis to establish the incidence of predefined content categories expected of the tabloid, pornographic and liberal press and, lastly, a theme-based content analysis that sought to establish the potential meanings and framing of the dominant content categories of gossip and sexualised copy. Overall, the study found Red Pepper to be a misogynistic tabloid, having elements said to belong to pornography and homophobia. According to the findings, not only does Red Pepper fall short of a liberal understanding of a newspaper in terms of diversity of topics, provision of information and professional practice, it also does not fit the understanding of an alternative public sphere, mainly because it fails to challenge the patriarchal framing of sex, sexuality and gendered relations. This framing is undertaken deliberately as a means to securing economic rather than journalistic ideals to which the editors pay lip service. Consequently, the gossip and sexualised content are not problematised and as such discourses and power relations therein are not interrogated. Neither are inadequacies in local systems addressed nor corrective action mobilised as expected of some tabloids. All in all, the publication fronts superficial entertainment content that echoes particular gender constructions and patriarchal commonsense and entrenches the (undesirable) status quo which, ironically, it claims to challenge.
Keywords: Red Pepper (Uganda); Sex in mass media -- Uganda; Liberalism in mass media -- Uganda; Homophobia -- Press coverage -- Uganda; Mass media -- Political aspects -- Uganda; Tabloid newspapers -- Uganda -- Case studies; Newspapers -- Uganda -- 21st century; Journalism -- Uganda